Interest Rate Adjustment Mechanisms as a Response to External Shocks: Evidence from Argentina's Convertibility Plan (1991-2002) - Farber, Vanina (Pontificia Universidad Católica del Perú. CENTRUM, 2010)
From 1991 to 2002, Argentina engaged in an economic stabilization strategy, the “Convertibility Plan,” that fixed the national currency to the U.S. dollar. This article analyzes how the counter-cyclical role of domestic interest rates contributed to the Plan’s collapse, as it changed investors’ confidence in the commitment of policymakers to continue with unpopular recessionary and deflationary adjustment policies. To reach this conclusion, this article – using univariate and multivariate techniques (cointegration) with monthly data from 1991 to 2002 – examines the dynamic behavior of domestic inflation and interest rates in the context of the currency board. In the absence of nominal exchange rate flexibility, other variables adjusted to ensure equilibria in both the goods and services and the capital markets. Following a similar dynamic to the one analyzed under the Convertibility Plan, and taking into consideration the finding that Argentine prices adjust to keep the real exchange rate constant in the long run, the current strategy of keeping a “competitive exchange rate” has an obvious downside: the impossibility to control inflation.
Keywords: Argentina; Cointegration; Convertibility Plan; PPP; UIP; https://purl.org/pe-repo/ocde/ford#5.02.04